2020
DOI: 10.1002/ghg.2006
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of polysulfone/diisopropylamine 1‐alkyl‐3‐methylimidazolium ionic liquid membranes: high pressure gas separation applications

Abstract: Membrane separation is gaining great attention in many applications, especially in gas separation. Polysulfone (PSF) is the most widely studied polymeric membrane material for CO2 in its pure or modified state. Ionic liquids supported membrane technology (SILMs) are now widely applied due to their unique properties at room temperatures. In our previous study, we proved the enhanced ability of ionic liquid enhanced PSF for the separation of CO2 from gas streams. In this study, the dielectric measurements (BDS) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 49 publications
3
4
0
Order By: Relevance
“…This value was close to that (190–200°C) of most literatures 29,32,33 . The literature reported that the T g value of the PSF membrane was 142°C 34 . The T g value of the CM‐ PSF membrane decreased to 173°C, and the T g value of the T‐PSF membrane further decreased to 158.24°C.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…This value was close to that (190–200°C) of most literatures 29,32,33 . The literature reported that the T g value of the PSF membrane was 142°C 34 . The T g value of the CM‐ PSF membrane decreased to 173°C, and the T g value of the T‐PSF membrane further decreased to 158.24°C.…”
Section: Resultssupporting
confidence: 86%
“…close to that (190-200 C) of most literatures. 29,32,33 The literature reported that the T g value of the PSF membrane was 142 C. 34 The T g value of the CM-PSF membrane decreased to 173 C, and the T g value of the T-PSF membrane further decreased to 158.24 C. This phenomenon was reported in literature 27 : The T g value of CM-PSF decreased from 183 to 158 C, which depended on the grafting degree. Higher grafting degree resulted in lower glass transition temperature.…”
Section: Thermal Behavior Of the Membranesmentioning
confidence: 65%
“…Moreover, there are some peaks of THF and CF-casted membranes appeared at 2851, 2870, 2927, 3037, and 3096 cm −1 . The peaks of 2851, 2870, and 2927 refer to C-H stretching in the alkene group in THF-casted membrane or CF-casted membrane as well [31]. Overall, it can be seen that intensities of THF peaks are higher than the intensities of CF peaks.…”
Section: Characterizationmentioning
confidence: 90%
“…Khraisheh et al [97] used microporous polysulfone matrix (PSF) impregnated with different concentrations of ionic liquids: 1-Ethyl-3-methylimidazolium hexa fluorophosphate ([Bmim][PF 6 ]) and bis(trifluoromethylsulfonyl) imide ([Emim][Tf 2 N]). The small addition of IL to the PSF matrix enhanced both CO 2 permeability and selectivity.…”
Section: Membrane Separationmentioning
confidence: 99%